China's reform of socialism on trial - Armin Bohnet; Günter Jaehne (Intereconomics, 1986)
Western public opinion frequently voices uncritical applause for the economic reforms in the People's Republic of China. The expectation of large sales opportunities in the Chinese market has led to a kind of China-euphoria in certain business circles. This frequently overlooks the fact that there are a wide variety of problems in implementing the reforms, which still have to be truly put to the test.
Keywords: 330; China